Dynamics of Cu, Mn, Ni, Sr and Zn release during decomposition of four types of litter in headwater riparian forests in northern Poland - Jonczak, Jerzy; Parzych, Agnieszka; Sobisz, Zbigniew (Leśne Prace Badawcze, 2014)
The aim of the study was to compare the dynamics of Cu, Mn, Ni, Sr and Zn release during decomposition of leaves of Black alder (native material), Norway maple, Red oak and European beech (exogenous material) in the area of headwater riparian forests along the upper course of the Kamienna Creek (Northern Poland). Litter bag method was used in the experiment. Initial materials differed in terms of their chemical composition. Cu, Mn, Ni, Sr and Zn contents were low in general, and in fact, even a few times lower than limit values for decomposition rate. Different trends in the dynamics of the leaf metal content during decomposition were observed in particular tree species despite the fact, that every materials were exposed in the same site. Release dynamics was strongly affected by the content of metals in initial materials and in topsoil. Accumulation of Cu, Mn and Zn was observed during decomposition of poorest in the elements maple leaves, as well as Ni in alder leaves and Sr in the leaves of maple, alder and oak. In beech leaves we observed intensive leaching of Ni, whereas downward trends in the Cu concentration of beech leaves, as well as Mn and Zn in beech and oak leaves, were related to weight loss of the leaves. In some cases, the dynamics of metal release displayed a more complicated two- or three-stage character (release of Ni from maple and oak leaves; Cu from maple leaves; Sr from alder, maple and oak leaves; and Zn from alder and maple leaves).